Relationship Between Body Image and Eating Behavior Among High School Female Adolescents - Widya Lionita; Fatmalina Febry; Yeni Anna Appulembang; Rini Anggraini (Jurnal Promosi Kesehatan Indonesia, 2022)
Background: Physical and psychological alteration during adolescence could determine adolescents’ nutritional status, especially for female adolescents. The Indonesian Ministry of Health estimated about 26.5% of female adolescents aged 12 – 18 years in South Sumatera Province were at risk of chronic energy deficiency in 2017. One of the direct predictors which affect nutritional status is eating behavior. The research aims to describe perceived body image and eating behavior of high school female adolescents and find the correlation between these variables.Method: The research applied a cross-sectional design and chose respondents purposively with inclusion criteria i.e., female adolescents at 1st and 2nd grade from four different high schools in Palembang. About 138 respondents completed the questionnaires of body image and eating behavior. The data were analyzed using a chi-square test on SPSS Application.Results: The majority of respondents (55.80%) were not satisfied with their own body shape. Above 15%  were on a diet. However, the respondents’ perception of body image was mostly classified as positive (54.35%), and they also had good eating behavior (56.52%). Body image significantly impacted eating behavior (p = 0.035). Those with positive body image are possibly at 2.210 times chances of having good eating behavior (95%CI: 1.112 – 4.391). Female adolescents have to build self-appreciation, not only based on their physical appearance. The health nutritionists should work together with the government to facilitate them to practice healthy eating behavior which may improve their nutrition status.